2017
DOI: 10.1002/brb3.704
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine‐prevented learning and memory impairment in REM sleep‐deprived rat is modulated by DREAM protein in the hippocampus

Abstract: Introduction REM sleep deprivation is associated with impairment in learning and memory, and nicotine treatment has been shown to attenuate this effect. Recent studies have demonstrated the importance of DREAM protein in learning and memory processes. This study investigates the association of DREAM protein in REM sleep‐deprived rats hippocampus upon nicotine treatment.MethodsMale Sprague Dawley rats were subjected to normal condition, REM sleep deprivation and control wide platform condition for 72 hr. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…However, in our study, we detected deterioration in probe performance of MWMT in the 48-h RD group. It is mainly in line with the study: Abd Rashid et al (2017) showed that 72-h RD in adult Wistar rats impaired learning and memory performance at MWMT. Some other studies also indicated that sleep restriction and RD diminished memory performance in the MWMT test (Saygin et al, 2017;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…However, in our study, we detected deterioration in probe performance of MWMT in the 48-h RD group. It is mainly in line with the study: Abd Rashid et al (2017) showed that 72-h RD in adult Wistar rats impaired learning and memory performance at MWMT. Some other studies also indicated that sleep restriction and RD diminished memory performance in the MWMT test (Saygin et al, 2017;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Many researchers have used the inverted flowerpot technique (Abd Rashid, Hapidin, Abdullah, Ismail, & Long, 2017; Joukar, Ghorbani‐Shahrbabaki, Hajali, Sheibani, & Naghsh, 2013; Siran et al., 2014; Thamaraiselvi et al., 2012). Although studies using a similar method were carried out to determine the association between REM sleep deprivation and the cardiovascular system, there was no study looking at the effects on the aorta.…”
Section: Discussionmentioning
confidence: 99%